BASED ON MATLAB AND EXCEL PROGRAMMING AND DEVELOPMENT THE NEW METHOD OF HEADING MACHINE CUTTING HEAD - ZHAO LiJuan; BAO WenJie; MA Qiang; ZHAO MingYang; LIU XuNan (Jixie qiangdu)
Using MATLAB and EXCEL joint programming developed longitudinal roadheader cutting head design software,according to the existing conditions of tunneling face cutting head kinematics parameters necessary input through the cut,cut tooth can automatically generate the corresponding arrangement diagram,load curve and cutting diagram,obtain the cutting head shape,leaf number of head and pick arrangement parameters relationship mode and cutting power,cutting energy consumption ratio,cutting resistance and cutting area between,for the design and optimization of cutting head provides a new method. In the engineering objects of type EBZ220 machine for cutting head shape,leaf Numbers,and cutter tooth arrangement design and select the optimal scheme,the universality and simplicity of the software